Interspecific variation in the diet of a native apex predator and invasive mesopredator in an alpine ecosystem. (25th June 2022) - Thompson, Eilysh R.; Driscoll, Don A.; Venn, Susanna E.; Geary, William L.; Ritchie, Euan G.
Abstract: Carnivores have key ecological roles in structuring and regulating ecosystems through their impacts on prey populations. When apex‐ and meso‐predators co‐occur in ecosystems, there is the potential for complex interspecific interactions and trophic dynamics that can affect the composition and functioning of ecological communities. Investigating the diet of sympatric carnivores can allow us to better understand their ecological roles (e.g. potential suppression of herbivores) or impacts (e.g. predation of threatened species). Australia's alpine region provides an ideal system in which to explore spatial and temporal variation in predator and prey interactions, using the dingo ( Canis dingo ) and invasive red fox ( Vulpes vulpes ) diet. We examined the diet of dingoes and foxes across three different mountains and seasons in Victoria's alpine region, using macroscopic scat analysis. There was little diet overlap between the two carnivores, with foxes having a broader diet than dingoes. Dingoes primarily consumed larger mammal species, including invasive sambar deer ( Cervus unicolor, 44%), and the native common wombat ( Vombatus ursinus, 34%), whereas foxes typically consumed smaller mammals, including the native bush rat ( Rattus fuscipes, 55%), and the invasive European rabbit ( Oryctolagus cuniculus, 15%). Dingoes consumed more than thirty times the volume of large invasive mammals (predominantly sambar deer) than did foxes. Foxes consumed close to 15 times as many critical weight range individuals per scat than dingoes. Only one threatened critical weight range mammal species was identified within scats, the broad‐toothed rat ( Mastacomys fuscus ), found within five fox scats. Our results suggest that the introduction of novel prey may alter predator–predator interactions by causing a reduction in the dietary overlap. Therefore, in the context of integrated wildlife management and biodiversity conservation, any control of novel, invasive prey populations needs to consider possible flow on effects to apex‐ and meso‐predator diets and potential secondary impacts on native prey.